The Influence of Business Incubators on Interest in Entrepreneurship with Entrepreneurial Attitudes as an Intervening Variable - Salim, Agus; Wardhana, Ery Tri Djatmika Rudijanto Wahju; Restuningdiah, Nurika (PT. EQUATOR SINAR AKADEMIA, 2024)
This study delves into the profound impact of business incubators, specifically focusing on the `Ships' Business Incubator in East Java, on fostering entrepreneurial interest and shaping entrepreneurial attitudes among its members. Identified challenges include a low inclination towards entrepreneurship among incubator members, attributed to factors such as fear of failure and a lack of entrepreneurial knowledge. The primary objective of the research is to design targeted educational and coaching strategies within business incubators to enhance interest in entrepreneurship by cultivating entrepreneurial attitudes. The research contributes to the existing literature by filling gaps in understanding the comprehensive impact of business incubators, especially within local contexts such as East Java. Using quantitative methods, the study encompasses a population of 580 members from the East Java 'Ships' Business Incubator, with a sample size of 220 individuals selected through proportionate stratified random sampling. The study concludes that the 'Ships' Business Incubator not only serves as a launchpad for businesses but also effectively fosters and sustains the entrepreneurial interests and attitudes of its members